Animation Concept as a Media to Increase Awareness of Gender-Based Violence against Women with Intellectual Disabilities - Suciady, Kezia; Sutanto, Ryan; Yudani, Hendian (The Center for Disability Studies and Services Brawijaya University, 2023)
Gender-Based Violence (GBV) continues to be a global issue that disproportionately affects women from all walks of life. Awareness and recognition of GBV in Indonesia keeps increasing, yet the attention on how it impacts women with disabilities is dangerously low. This design aims to present a solution to socialize the issue towards the general public of Indonesia. This is a qualitative descriptive research, data gathering was done in the form of interviews with important figures in the correlating fields, as well as a focus group discussion with individuals representing the target audience. Findings revealed a shortage in resources when handling GBV cases against women with Intellectual Disabilities (ID), a lack of participation from the Indonesian governmental body in aiding victims, along with a substantial interest towards a short animation video posted on YouTube with the addition of promotion on Instagram and TikTok as a socialization media and method. Keywords: gender-based violence, intellectual disability, qualitative descriptive research, animation, socialization